2004
DOI: 10.1074/jbc.m407850200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutagenesis of the Angiogenic Protein CCN1 (CYR61)

Abstract: The matricellular protein CCN1 (CYR61) regulates multiple cellular processes and plays essential roles in embryonic vascular development. A ligand of several integrin receptors, CCN1 acts through integrin ␣ 6 ␤ 1 and heparan sulfate proteoglycans (HSPGs) to promote specific functions in fibroblasts, smooth muscle cells, and endothelial cells. We have previously identified a novel ␣ 6 ␤ 1 binding site, T1, in domain III of CCN1. Here we uncover two novel 16-residue sequences, H1 and H2, in domain IV that can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…In accordance with these results, we have previously reported that CYR61 can regulate the levels of a v b 3 expression as well as breast cancer cell sensitivity to taxol-induced cell damage in an HER2/neu-independent fashion (Menendez et al, 2004). CYR61 is also an important growth regulator in endothelial cells, mainly through its binding with the cell surface integrins a v b 3 and a 6 b 1 (Leu et al, 2002(Leu et al, , 2004. Since integrin ligation is required for endothelial cells responses to most proangiogenic factors (Stupack and Cheresh, 2003), it is reasonable to offer a model in which the HRG/CYR61/a v b 3 molecular connection may be orchestrating breast tumorigenesis and progression in at least two concerted modes: (1) by regulating endothelial cells survival and recruitment during tumor neovascularization in a paracrine fashion through an a v b 3 -dependent mechanism; and (2) by promoting breast cancer epithelial cell proliferation in an autocrine/paracrine manner either by increasing the activity of other growth factors (i.e.…”
Section: Hrg Regulates a V B 3 Expression In Breast Cancer Cellssupporting
confidence: 63%
“…In accordance with these results, we have previously reported that CYR61 can regulate the levels of a v b 3 expression as well as breast cancer cell sensitivity to taxol-induced cell damage in an HER2/neu-independent fashion (Menendez et al, 2004). CYR61 is also an important growth regulator in endothelial cells, mainly through its binding with the cell surface integrins a v b 3 and a 6 b 1 (Leu et al, 2002(Leu et al, , 2004. Since integrin ligation is required for endothelial cells responses to most proangiogenic factors (Stupack and Cheresh, 2003), it is reasonable to offer a model in which the HRG/CYR61/a v b 3 molecular connection may be orchestrating breast tumorigenesis and progression in at least two concerted modes: (1) by regulating endothelial cells survival and recruitment during tumor neovascularization in a paracrine fashion through an a v b 3 -dependent mechanism; and (2) by promoting breast cancer epithelial cell proliferation in an autocrine/paracrine manner either by increasing the activity of other growth factors (i.e.…”
Section: Hrg Regulates a V B 3 Expression In Breast Cancer Cellssupporting
confidence: 63%
“…3a), indicating that CCN1 can induce senescence as a cell adhesion substrate and this activity is unique among the ECM proteins tested. Consistent with impaired senescence in Ccn1 dm / dm mice, purified DM protein26 was completely unable to inhibit DNA synthesis, induce SA-β-gal expression, or trigger the SASP/SMS (Fig. 3b–d; Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Recombinant CCN1 and mutant proteins (D125A and DM) were produced using a baculovirus expression system in insect cells and purified by ion-exchange or immuno-affinity chromatography22, 26. Human FN, VN, mouse LN, rat tail Col.I were from BD Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…CCN1 is a secretory integrin-binding protein that regulates angiogenesis, cell adhesion, migration, proliferation, survival and apoptosis (Chen et al, 2001;Leu et al, 2004). Alternatively, CCN1 has a complex role in tumorigenesis, showing divergent functions and expression profiles in cancers from different tissues (O'Kelly, 2005).…”
Section: Introductionmentioning
confidence: 99%